Murder at Wakehurst - Maxwell, Alyssa (Maxwell, Alyssa. Gilded Newport mystery., 2021)
When she stumbles upon a dead body with an arrow in it while attending a lavish Elizabethan fête in 1899, journalist Emma Vanderbilt, discovering the victim is a judge who didn't walk the straight and narrow, must score a bull's eye to stop the killer from taking another life.